Permissible monopoly in Islamic law - Rashid , Ahmed; Rashid , Sarah (Islamic Sciences Journal, 2023)
Monopoly carries with it the seeds of doom and destruction because of the injustice, intransigence, high prices and affliction it causes, and the waste of freedom of trade and industry, and blocks the outlets for work and the doors of livelihood. What they possess until the price rises and they sell at a great profit without fear of Allah and care for the poor and needy of the nation. This phenomenon I witnessed in my wounded country, Iraq. Scholars and scholars have always warned about it, but few respond. Monopoly enjoys one of the pillars of the modern capitalist system, and a feature of economic dealings in most of the countries. Companies, if not in all of them, although it carries with it the seeds of destruction and destruction because of what it causes in injustice, intransigence, high prices, and affliction.